Managing the Unmanageable: Crisis Management - Ramely, Asmahany; Foo, Yen Sin; Mat Yusof, Noor Amalina; Ahmadd, Rozila; Tan, Nick Yeet Fhong (2023)
This case study delves into the remarkable journey of QLIC Solution Sdn Bhd, an event management company led by its visionary founder, Nick Tan Yeet Fhong. The study explores the profound impact of the COVID-19 crisis on QLIC Solution's operations, the challenges faced during the pandemic, and the company's exceptional ability to adapt and innovate to thrive amid adversity. Additionally, the research sheds light on the unexpected opportunities that arose from the crisis and how QLIC Solution's proactive approach to crisis management brought added value to the event management industry. QLIC Solution's resilience and resourcefulness not only allowed them to survive but also positioned them as a saviour for other businesses seeking to rescale and upscale. The case study highlights the importance of digital transformation, strategic partnerships, and reskilling in navigating crises and achieving sustainable growth. QLIC Solution's journey serves as an inspiring example for businesses seeking to embrace change, capitalise on emerging trends, and create a resilient and customer-centric approach in an ever-evolving market landscape.